PENGARUH STRUKTUR KEPEMILIKAN TERHADAP KEBIJAKAN DIVIDEN PERUSAHAAN - Felicia Wuisan; Fransiskus Randa; Lukman Lukman (SIMAK, 2018)
This research aims to examine the effect of ownership structure on dividend policy. In this research ownership structure consists of managerial ownership, government ownership, foreign ownership and family ownership. The population used is a non-financial company that listed in Indonesian Stock Exchange (BEI) research period 2012-2016. The number of samples used in this research is 242 data of the company year. Sampling technique used is purposive sampling. Data analysis used was multiple regression analysis method. The empirical result of this research indicate that managerial ownership has a positive but not significant effect on dividend policy; government ownership has a negative and significant effect on dividend policy; foreign ownership has a positive and significant effect on dividend policy; and family ownership has a negative and significant effect on dividend policy.